Problems, issues, and prospects of language teaching in the context of bilingual policy - Pascacio, Emy M. (Education quarterly.)
Successful implementation of the bilingual policy can only be achieved through the concerted effort and time given by the teachers, administrators, policymakers in the Ministry of Education and Culture, and more government subsidy. If human resources development is important for nation building the Philippine educational system should be one of the top priorities in terms of government funding. A master educational plan including a timetable for its implementation with the corresponding funds is urgently needed or else the educational problems will remain with us forever.